Competitive and Comparative Advantages Analysis of Organic Rice Farming in Karanganyar Regency, Central Java Province - Anita Suharyati; Slamet Hartono; Lestari Rahayu Waluyati (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2016)
In era of the free trade which increasingly competitive, it is important to understandthe competitiveness of foodstuff commodity by every country. Public awareness of health hazards and adverse environmental impacts, as well as the trend of consumers choosing safe foodstuffs, lead to a shift to the cultivation of organic systems. This paper uses Policy Analysis Matrix (PAM) analysis to determine whether rice farming system has a comparative and competitive advantages when produced with organic farming practices. The purposes of this paper are to (1) Analyse the financial and economic advantages of organic rice farming in Karanganyar. (2) Analyse competitiveness of organic rice in Karanganyar Regency viewed from competitive advantage and comparative advantage. Based on the data analysis,results show that the organic rice farming in Karanganyar Regency has a competitive advantage and comparative advantage, indicated by PCR and DRC value that is less than one. The competitive advantage of organic rice in Karanganyar Regency is greater than the comparative advantage. PCR coefficient amount of 0.74 and DRC coefficient amount of 0.56. Thus organic rice farming in Karanganyar Regency is worth developing and has good competitiveness in domestic market as well as international market.